Risk Analysis of Project Owners As Actors in the Procurement of Government Goods and Services in Construction Work - Arief Adrian; Benny Hidayat; Taufika Ophiyandri (CIVED, 2025)
In the implementation of PBJP construction work, potential risks that can affect the achievement of PBJP goals, namely producing the right goods/services according to the budget, but this has still not been researched in the Agam Regency area. Therefore, this study aims to identify and analyze the risks that can occur to Project Owners/Owners (PBJP) in the implementation of construction in the area. The risk identification method was carried out through a pilot survey of project owners as well as previous literature studies. Meanwhile, the risk assessment was carried out using a questionnaire distributed to PBJP actors, referring to the Australian/New Zealand Risk Management standard (AS 4360). Risks are grouped based on their risk levels at various stages, namely planning, procurement, selection, election implementation, and handover. The results of the risk assessment showed that there were no risks with extreme categories, but there were 10 risks with high categories, 53 risks with medium categories, and 1 risk with low categories. The results of this study are expected to contribute to the development of construction risk management policies and practices in the Agam Regency area, as well as provide new insights in research related to PBJP in other areas that have similar characteristics.